Uterine torsion: A case report - Prabhakar, Sonil; Gupta, Pratiksha (Nepal Journal of Obstetrics and Gynaecology, 2010)
In uterine torsion, the uterus twists more than 45 degrees around its long axis at the junction between the cervix and the corpus. Probably due to rarity only few cases are reported where detorsion was either not possible or posterior uterine wall opening, more tactfully incisions inflicted transversely, have been the only way out. Reported herewith is a 26 yr, third gravida at 38 weeks pregnancy, with previous caesarean in early labour and underwent cesarean for rupture of the membrane, was realized to have an incision inflicted in the posterior wall of the uterus, 3 cm above the disposition of uterosacral ligament amidst severe torsion of the uterus that was successfully detorted avoiding hysterectomy, in view of the young age. Key words: uterine torsion; term pregnancy complication; uterine rotation. DOI: 10.3126/njog.v4i1.3335 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 55-57